Pengembangan Media Pop Up Story Book Berbasis Kearifan Lokal Pada Materi Membaca Pemahaman Siswa Kelas IV UPT SDN Kademangan 01 - Nanda Saniyaroh; Isna Khuni Mualimah; Ragil Tri Oktaviani (Lembaga Pengembangan Kinerja Dosen, 2026)
This study was conducted to develop a local wisdom-based Pop-Up Story Book as a learning medium for improving reading comprehension skills among fourth-grade students at UPT SDN Kademangan 01, Blitar Regency, as well as to examine its validity and effectiveness. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants consisted of 20 fourth-grade students of UPT SDN Kademangan 01. Data collection was carried out through material expert validation sheets, media expert validation sheets, language expert validation sheets, teacher response questionnaires, and pre-test and post-test assessments. The findings indicated that the developed learning media met the criteria of high validity, obtaining validation scores of 82% from material experts, 90% from language experts, and 90% from media experts. In addition, the teacher response questionnaire yielded a score of 93.4%, indicating that the media was highly effective for classroom use. The effectiveness of the media was further supported by a substantial improvement in students’ reading comprehension performance. The average score increased from 47.00 on the pre-test to 91.00 on the post-test. Statistical analysis using the One-Sample T-Test produced a significance value of 0.000, which was lower than the threshold of 0.05, demonstrating a significant effect of the developed media on students’ reading comprehension achievement. Based on these findings, the local wisdom-based Pop-Up Story Book can be considered a valid, effective, and suitable learning medium for elementary school students while simultaneously promoting local cultural values through the story of Kyai Bonto Kademangan.